2001
DOI: 10.1191/096120301675973164
|View full text |Cite
|
Sign up to set email alerts
|

Non-thyphoidal salmonellosis in patients with systemic lupus erythematosus. A study of fifty patients and a review of the literature

et al.

Abstract: The objective of this study was to characterize the clinical profile of lupus patients with non-typhoidal salmonellosis. A retrospective review of the clinical charts of lupus patients diagnosed with bacteriologically proven non-typhoidal salmonellosis over the last 20 y was undertaken, paying special attention to risk factors, clinical presentation and treatment outcome. Most episodes were bacteraemic without a localizing focus; and some patients were afebrile. They usually occurred in patients prone to oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 22 publications
(39 reference statements)
1
37
0
1
Order By: Relevance
“…6 Another study of 17 patients, who in this instance had prosthetic-valve NTS endocarditis, found that aortic valve prostheses were more frequently affected than were mitral valve prostheses. 6,33 Other valvulopathies associated with NTS endocarditis include rheumatic valve disease, myxoid mitral valve disease, and degenerative valve disease. Postinfarction ventricular aneurysms also predispose patients to mural endocarditis, which is characterized by extensive infections spreading from endocardium to pericardium-with pseudoaneurysm and abscess formation.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Another study of 17 patients, who in this instance had prosthetic-valve NTS endocarditis, found that aortic valve prostheses were more frequently affected than were mitral valve prostheses. 6,33 Other valvulopathies associated with NTS endocarditis include rheumatic valve disease, myxoid mitral valve disease, and degenerative valve disease. Postinfarction ventricular aneurysms also predispose patients to mural endocarditis, which is characterized by extensive infections spreading from endocardium to pericardium-with pseudoaneurysm and abscess formation.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…6,8,9,26,27,32 Investigators in one NTS-SLE study determined that 83% of Salmonella infections occurred during periods of active SLE, but it was unclear if this was due to the SLE itself or to the more aggressive immunosuppressant therapy given to those affected. 33 Patients with SLE who have been treated with prednisolone, cyclophosphamide, azathioprine, or methotrexate are more predisposed to NTS septicemia and endocarditis than are patients who do not receive immunoregulatory medication. [6][7][8]33 Structural Heart Disease In the previously mentioned 1978 review, 10 83% of Salmonella endocarditis patients younger than age 50 had underlying valvular disease with predominantly mural (rather than valvular) lesions.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases of salmonellosis have been reported among SLE patients. [2][3][4] In fact, SLE was cited as the most frequent underlying disease for salmonella bacteremia among hospitalized patients. 5 In addition to steroids and cytotoxic drugs, other factors which enhance this susceptibility include abnormal functioning of mononuclear phagocytic systems due to previous occupation of Fc receptors by circulating immune complexes, or complement consumption resulting in decreased serum opsonizing activity, functional hyposplenism and haemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, retrospectively reviewing 50 SLE patients diagnosed with bacteriologically proven non-typhoidal salmonellosis over a 20-year period, it was found that most episodes were bacteraemic without a localising focus, and some patients were afebrile. Mortality in general occurred from concomitant septic shock and major organ failure from active lupus (mainly renal) [22]. It is noteworthy that osteomyelitis of the long bones due to salmonella can occur in SLE patients [23].…”
Section: Salmonellamentioning
confidence: 99%